SPH numericalapproach in modelling 2D muddy debris flaw - minatti, L.; pasculli, A. (Italian journal of engineering geology and environment, 2011)
2D muddy debris flow has been simulated according to a dam break like problem along a slope. The two sets of equations related to the fluid and solid phases, as considered by the debris flow mixture theory, have been simpli ed in only one set of equations, considering just one equivalent material. Then the Herschel-Bulkley fluid constitutive equations have been selected. The correct parameters of the HeRsCHel-bulkley model have been chosen in order to correctly simulate the behaviour of mud flows. The final mathematical model, has been solved numerically with the smoothed particle hydrodynamics (SPH) method. SPH is a particle mesh-free Lagrangian method, well suitable for computing highly transitory free surface flows of complex fluids in complex geometries. Finally a laboratory experimental test has been selected for comparison. Satisfactory results have been achieved. Nevertheless, further parametric analyses will be carried out and further considerations about both constitutive equations and numerical improvements will be employed and discussed in future papers.